Pancreatic lipase inhibitory potential of selected Malaysian plants - Alias, Norsyuhada; Leow, Thean Chor; Mohamad Ali, Mohd. Shukuri; Ahmad Tajudin, Asilah; Salleh, Abu Bakar; Raja Abd. Rahman, Raja Noor Zaliha (Universiti Kebangsaan Malaysia (UKM), Malaysia, 2014)
Pancreatic lipase inhibitors from natural sources are considered as potential tool for the treatment of obesity. The inhibitory activity of 24 crude extracts of selected Malaysian plants against porcine pancreatic lipase (PPL) was successfully screened and tested by using in vitro approach. Orthosiphon stamineus, Phyllanthus niruri, Murraya paniculata and Averrhoa bilimbi leaves extracts showed more than 70% inhibitions when incubated with PPL at a final concentration of 500 μg/mL for 15 minutes at 37⁰C. P. niruri crude extract exhibited strongest lipase inhibitory activity, with an IC50 value of 27. 65 μg/mL followed by O. stamineus, M. paniculata and A. bilimbi with IC50 values of 34.74, 41.45 and 55.18 μg/mL, respectively. Inhibition mode study disclosed that O. stamineus and A. bilimbi could act as uncompetitive inhibitor while P. niruri and M. paniculata could act as noncompetitive inhibitor. The results suggested that these four plant extracts may be useful for obesity treatment.